96-Week Results of Abacavir/Lamivudine versus Tenofovir/Emtricitabine, plus Efavirenz, in Antiretroviral-Naive, HIV-1-Infected Adults: Assert Study. Issue 7 (October 2013) - Moyle, Graeme J; Stellbrink, Hans-Jürgen; Compston, Juliet; Orkin, Chloe; Arribas, José R; Domingo, Pere; Granier, Catherine; Pearce, Helen; Sedani, Sangeeta; Gartland, Martin; ,
Background: Abacavir/lamivudine (ABC/3TC) and tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) are widely used as first-line antiretroviral therapies. However, there are limited data comparing the safety of these therapies with long-term use. The objective of this study was to assess the long-term safety of these commonly used first-line nucleoside/nucleotide combinations each administered with efavirenz (EFV). Methods: This open-label, 96-week, randomized study compared the safety (renal, bone and metabolic) and efficacy of ABC/3TC and TDF/FTC plus EFV in HLA-B*5701-negative antiretroviral-naive adults. Results: A total of 385 subjects were enrolled, and 249 (65%) subjects completed the study. The difference in changes from baseline in estimated glomerular filtration rate (calculated by the Modified Diet in Renal Disease equation) between treatment arms was not significant. There was a significant difference between the arms ( P <0.0001) for markers of tubular dysfunction (retinol-binding protein and ß-2 microglobulin) favouring ABC/3TC. Hip bone mineral density decreased from baseline in both arms, with a significantly greater decline with TDF/FTC (ABC/3TC -2.2% and TDF/FTC -3.5%; P <0.001 at week 96). Subjects in the ABC/3TC arm had greater increases from baseline in median total cholesterol, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol and triglycerides. Adverse events were similar between arms. The virological failure rate was low in both arms. Conclusions: ABC/3TC and TDF/FTC in combination with EFV minimally affected estimated glomerular filtration rate over 96 weeks. TDF/FTC was associated with greater increases in tubular dysfunction and bone turnover marker levels, greater decreases in hip bone mineral density, and smaller increases in serum lipid levels.